Best Answer

b = 0.2 x 10a = 2a

a/(2b) = a/(4a) = 1/4

= 25%

Q: If 20 percent of 10a is b then what percent of 2b is a?

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

Yes. For example, 7 - 3 = 4. You will always get an even number when adding or subtracting an odd and an odd. Let A & B be two odd numbers, so find out if A - B is even or odd. A = 2a +1 & B = 2b + 1 {little a & b are any integers, multiplying by 2 guarantees that 2a is even, then adding 1 will make it odd} A-B = 2a+1 - (2b+1) = 2a + 1 - 2b - 1 = 2a - 2b = 2(a-b). So (a-b) is some integer, but you multiply by 2, so the answer is even. Add A+B = 2a+1 + 2b+1 = 2a + 2b + 2 = 2(a+b+1), so again we are multiplying 2 by some integer, and get an even number.

Assuming the missing sign is "minus" then you have the difference between two squares. This is solved as (x + y)(x - y). In your example x = 4a and y = 2b so the factorisation is (4a + 2b)(4a - 2b) or more completely: (4)(2a + b)(2a - b).

9 and 10 First the main formulas: a+b=19 a-b=1 Find out what one of the variables are. We can choose "a" or "b" from either of the two formulas. Let's choose "a" from the a-b=1 formula. a - b = 1 [formula] a-b (+b) = 1 (+b) [solve for "a" by removing "b"] a = 1+b Plug that "a" into the other formula a+b=19. a + b = 19 (1+b) +b = 19 1 + 2b = 19 1 + 2b - 1 = 19 -1 2b = 18 b = 9 Plug that into our formula solved from before for "a" a = 1 + b a = 1 + (9) a = 10

280a4b2

(a2 + 2)(b + 3)

Related questions

10a - 10 b

2b-6=20 2b=26 b=26/2 b=13

The given terms can be simplified to: a -b

10a + b = 7(a + b) 10a + b = 7a + 7b 3a = 6b a = 2b (2,1), (4,2), (6,3), and (8,4) meet these requirements. So the numbers that are solutions are 21, 42, 63, and 84.

b/50 = 100*b/50 % = 2b per cent.

=2b

-b+5b-2b=2b

10a - 5b = 25 So 5b = 10a - 25 and hence b = 2a - 5

2a + 2b = 160 But b = a + 40 so 2a + 2(a + 40) = 160 ie 2a + 2a + 80 = 160 or 4a = 80 ie a = 20 Then b = a + 40 gives b = 20 + 40 = 60 Solution: a = 20, b = 60

a-b+a-b+2b+a = 4a

a-^2a-b^-a-b

a = 2b - c a + c = 2b (a+c)/2 = b b = (a+c)/2